Influencer authenticity and intention to co-create brand value: an investigation of central and peripheral pathways - Shermeen Hasan; Hasan Zahid; Abdul Qayyum (Cogent Business & Management, 2024)
Given the popularity of influencer marketing, this study aimed to determine the effectiveness of influencer authenticity in achieving intention to co-create brand value and purchase intention in Pakistan. Grounded in the Elaboration Likelihood Model, the study explored the central and peripheral routes to achieving desired behavioral intentions. Using a self-administered questionnaire, data were collected from 421 fashion and lifestyle social media influencers followers in Pakistan by the time-lagged approach, over a period of four months, and partial least squares structural equation modeling was performed for data analysis. The results showed a significant impact of influencer authenticity on behavioral intentions. Serial mediation indicated that consumers followed the central route of persuasion. The study aimed to fill gaps in the influencer marketing research literature by conceptualizing influencer authenticity as a composite higher-order construct and examining its impact on the intention to co-create brand value. Second, it elaborated on the cognitive and affective components of attitude formation using central and peripheral routes, respectively. Third, it highlighted relational attitude (the customer-brand relationship) as a bridge to achieving targeted behavioral intentions. The outcomes of this study may assist managers in designing effective influencer marketing campaigns by emphasizing brand attributes rather than relying on social media influencer followership.
Keywords: 650; Influencer marketing; influencer authenticity; attitude toward brand; attitude toward influencer; brand relationship; value co-creation